EFFECTIVENESS OF MULTISIM INTERACTIVE MULTIMEDIA APPLICATION AS DIGITAL TECHNIQUES LEARNING MEDIA IN SMK NEGERI 7 BALEENDAH - Nurzaman, Mochamad Zain (2013)
This study aims to determine the effectiveness of Multisim learning media on learning activities of Digital Technique lessons, hoping to have a positive impact on improving student learning outcomes in particular on basic competency of basic logic gates. The research method used is the method of research and development which conducted in three stages, that is: the preliminary studies, development studies, and evaluation studies. The subject of the research done by taking a sample of 30 students of class X Audio Video Engineering Majors SMK 7 Baleendah. Phase the preliminary studies conducted to collect data such as observation, interviews, and questionnaires. Phase of development studies conducted to develop and validate products such as the Multisim learning media. Finally, the stage of evaluation studies conducted to experimented products on a limited basis and evaluate research subjects in the form of pretest and posttest. The results showed that: 1) the level of students' understanding and interest in learning materials very less, due to the limited use of learning media. 2)This Multisim learning media can be effective, it is measured from the pretest-posttest with increased gain academic skills of students academic average achieve 0.35 on middle category. 3) The resulting product is Multisim program that has developed into learning media of digital techniques, and packaged in a CD Learning. 4) The use of Multisim learning media can improve student learning outcomes, and able to increase student interest against the Digital Technique lessons based on the results of student questionnaires with good qualifications. Keywords: Research and Development (R&D), Learning Media, Multisim, Digital